2016
DOI: 10.1007/s00018-016-2292-0
|View full text |Cite
|
Sign up to set email alerts
|

A cellular reporter to evaluate CRM1 nuclear export activity: functional analysis of the cancer-related mutant E571K

Abstract: The exportin CRM1 binds nuclear export signals (NESs), and mediates active transport of NES-bearing proteins from the nucleus to the cytoplasm. Structural and biochemical analyses have uncovered the molecular mechanisms underlying CRM1/NES interaction. CRM1 binds NESs through a hydrophobic cleft, whose open or closed conformation facilitates NES binding and release. Several cofactors allosterically modulate the conformation of the NES-binding cleft through intramolecular interactions involving an acidic loop a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 54 publications
3
49
0
1
Order By: Relevance
“…In fact, the molecular mechanisms that may be responsible for the pathogenic effect of XPO1 mutations remain to be established. Consistent with the location of the mutational "hotspot" proximal to the NES-binding site [ Figure 2B], it has been reported that the E571K mutation subtly increases the affinity of the receptor for some NESs with a negatively charged carboxy-terminal end [32] . Conceivably, this could lead to altered export of one or more cargos, whose mislocalization might in turn contribute to tumorigenesis.…”
Section: A Recurrent Xpo1 Gene Mutation In Hematological Malignanciessupporting
confidence: 82%
See 1 more Smart Citation
“…In fact, the molecular mechanisms that may be responsible for the pathogenic effect of XPO1 mutations remain to be established. Consistent with the location of the mutational "hotspot" proximal to the NES-binding site [ Figure 2B], it has been reported that the E571K mutation subtly increases the affinity of the receptor for some NESs with a negatively charged carboxy-terminal end [32] . Conceivably, this could lead to altered export of one or more cargos, whose mislocalization might in turn contribute to tumorigenesis.…”
Section: A Recurrent Xpo1 Gene Mutation In Hematological Malignanciessupporting
confidence: 82%
“…This experimental approach cannot be used to demonstrate XPO1-mediated export of proteins that are constitutively located to the nucleus. An alternative approach in this case could be ectopic overexpression of the receptor, which promotes export of NES-containing nuclear cargos to the cytoplasm [32] . Besides LMB-based experiments, the identification, validation and characterization of XPO1 cargos often involve biochemical analyses to demonstrate RanGTP-dependent binding, as well as mutagenesis to map the NES.…”
Section: Xpo1-mediated Protein Nuclear Export: Cargos Mechanisms Andmentioning
confidence: 99%
“…Indeed, the change from a negatively charged (glutamate) to a positively charged (lysine) residue could modify the affinity of XPO1 for NESs bearing negative charges [27]. proteins.…”
Section: Discussionmentioning
confidence: 99%
“…We utilized a cellular reporter containing one of the NESs to evaluate the sequencespecific effects of XPO1 hotspot mutations on nuclear export, which were suggested by the structural and proteomic analyses above. We used a modi fied version of a previously described nuclearexport reporter (40) where the first 100 amino acids of the XPO1 substrate survivin (bearing its NES) are fused to a 3× FLAG epitope and two nuclear localization signals ( Supplementary Fig. S9A).…”
Section: Xpo1 E571k Mutations Alter Nes Recognition In a Sequence-spementioning
confidence: 99%